Manajemen Kurikulum Merdeka Dalam Penguatan Profil Pelajar Pancasila Dan Profil Pelajar Rahmatan Lil ‘Alamin - Widihastuti, Fithriyah; Muhdi, Muhdi; Nurkolis, Nurkolis (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
This study aims to investigate and analyze the Independent Curriculum in MI Taufiqiyah, especially related to P5PPRA, with a focus on planning, organizing, implementing, and supervising. The research questions include the process of planning, organizing, and implementing the integration of Pancasila and Rahmatan Lil Alamin values, as well as the supervision mechanism of the Independent Curriculum. The method used is qualitative with a phenomenological approach, including interviews, observations, and documentation. Data analysis includes collection, reduction, presentation, and conclusion drawn. The results of the study show progress in the management of the Independent Curriculum for P5PPRA at MI Taufiqiyah. At the planning stage, intensive socialization is carried out to prepare teachers. At the organizing stage, infrastructure evaluation and improvement of teacher competence through collaboration with the Central Java Religious Education and Training Center were carried out, as well as the formation of a team of facilitators for daily activities and cooperation with the Agriculture Office for the urban farming program. The implementation of P5PPRA as planned involves practical activities, despite facing challenges in knowledge. Supervision shows obstacles in processing and reporting the results of student character assessments, with the need to increase the involvement of the Ministry of Religion of Semarang City. MI Taufiqiyah shows a strong commitment to developing students' character through continuous evaluation and active stakeholder engagement.